Revision of the flightless click-beetle genus Neodima Schimmel & Platia (Elateridae: Dimini) endemic to China, with comments on its systematic position - Kundrata, Robin; Sormova, Eliska; Qiu, Lu; Prosvirov, Alexander S. (Zootaxa, 2019)
Distribution of flightless insect lineages often help us to identify the areas of long-term stability which serve as biodiversity hotspots. In this paper we taxonomically revise the wingless click-beetle genus Neodima Schimmel & Platia, 1992 endemic to the mountainous regions of Sichuan, China. Neodima sichuanensis Schimmel & Platia, 1992 and N. cechovskyi Schimmel, 1998 are redescribed, and N. belousovi Prosvirov & Kundrata sp. nov. is described as new for science. The distribution and morphological diversity of Neodima is discussed, main diagnostic characters for all species are figured, and an identification key to the species of this genus is provided. Mouthparts as well as female pregenital segments and genitalia are described and figured for the first time for this genus. Further, we compare Neodima to morphologically similar genera, and discuss its systematic position within Dimini.